Perlindungan Hukum bagi Pekerja Anak di Indonesia - Made Dharma Laksana Swastika; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
Child labor regulations in Law 13/2003 for child labor in a company can be said in practice to be quite good and in accordance with their respective work agreements and there must be permission from the child's parents. This study aims to determine the legal protection for child labor in Indonesia and determine the factors causing underage children to do work. This research was designed using empirical legal methods. Sources of data obtained directly from the community called primary data (basic data) and obtained from library materials called secondary data. Data was collected using documentation and interview techniques. The results of this study indicate that the regulation of child labor in the Law of the Republic of Indonesia Number 13 of 2003 for child labor in a company is in good practice and in accordance with the work agreement of each and there must be permission from the child's parents. In overcoming obstacles and obstacles, the company tries as much as possible to realize the core of article 68 of the Law of the Republic of Indonesia Number 13 of 2003 in terms of prohibiting the company from employing underage child labor by providing certain policies to be enforced after deliberation between the company and child labor first. Through this research, non-litigation settlement is expected as the first choice and authoritative (fair for both parties), namely Workers and Employers are given the freedom to choose an existing peace agent (conciliator/mediator), and facilitate the formation of an arbitration system that is free / independent, independent, and authoritative.